Efficient decomposition of organic compounds and reaction mechanism with BiOI photocatalyst under visible light irradiation - Li, Yongyu; Wang, Jianshe; Yao, Hongchang; Dang, Liyun; Li, Zhongjun (Journal of molecular catalysis. A, Chemical, 2011)
BiOI photocatalyst with efficient visible photocatalytic activity was synthesized by a precipitation–filtration process and consequent hydrothermal treatment, and its photodegradation mechanism was studied systematically. [Display omitted] ▶ BiOI photocatalyst was synthesized successfully. ▶ BiOI exhibits excellent photocatalytic activity. ▶ Photodegradation mechanism was investigated systematically. ▶ hvb+ and O2− radicals were proven to be the main oxidants. BiOI photocatalyst was synthesized by a precipitation–filtration process and consequent hydrothermal treatment. The as-prepared BiOI exhibits efficient photocatalytic activity on the decomposition of widely used model pollutants, methyl orange (MO) and phenol, under visible light irradiation. Even under the illumination of a compact fluorescent lamp, the obtained BiOI also exhibits high photocatalytic activity. The possible photodegradation mechanism was studied by the examination of active species HO, hvb+, or O2− anions through adding scavengers such as tert-butanol (t-BuOH), I− anion, bromate anion and benzoquinone (BQ). The results show that photodegradation of MO molecules is attributed to the action of hvb+ via direct hole oxidation process and the oxidation action of the generated O2− radicals. Dissolved oxygen play an important role in photocatalytic reaction, which could trap the photogenerated electrons to reduce the recombination of hvb+ and ecb− and also function as a precursor of main oxidant O2−. Hydroxyl radical was verified to be inappreciable for the decomposition of MO.